Fluorodeoxyuridine mediated cell cycle synchronization in S-phase increases the Auger radiation cell killing with 125I-iododeoxyuridine - Perillo-Adamer, F.; Kosinski, M.; Dupertuis, Y. M.; Viertl, D.; Bischof Delaloye, A.; Buchegger, F. (Nuklearmedizin - NuclearMedicine, 2009)
Aim:125I-iododeoxyuridine is a potential Auger radiation therapy agent. Its incorporation in DNA of proliferating cells is enhanced by fluorodeoxyuridine. Here, we evaluated therapeutic activities of 125I-iododeoxyuridine in an optimized fluorodeoxyuridine pre-treatment inducing S-phase synchronization. Methods: After S-phase synchronization by fluorodeoxyuridine, cells were treated with 125I-iododeoxyuridine. Apoptosis analysis and S-phase synchronization were studied by flow cytometry. Cell survival was determined by colony-forming assay. Based on measured growth parameters, the number of decays per cell that induced killing was extrapolated. Results: Treatment experiments showed that 72 to 91% of synchronized cells were killed after 0.8 and 8 kBq/ml 125I-iododeoxyuridine incubation, respectively. In controls, only 8 to 38% of cells were killed by corresponding 125I-iododeoxyuridine activities alone and even increasing the activity to 80 kBq/ml gave only 42 % killing. Duplicated treatment cycles or repeated fluorodeoxyuridine pre-treatment allowed enhancing cell killing to >95 % at 8 kBq/ml 125I-iododeoxyuridine. About 50 and 160 decays per S-phase cells in controls and S-phase synchronization, respectively, were responsible for the observed cell killing at 0.8 kBq/ml radio-iododeoxyuridine. Conclusion: These data show the successful application of fluorodeoxyuridine that provided increased 125I-iododeoxyuridine Auger radiation cell killing efficacy through S-phase synchronization and high DNA incorporation of radio-iododeoxyuridine.
Keywords: Auger radiation treatment; 125I-iododeoxy-uridine; fluorodeoxyuridine; cell cycle synchronization; glioblastoma